Association between fat-soluble vitamins and self-reported health status: a cross-sectional analysis of the MARK-AGE cohort. Issue 3 (14th August 2022) - Stokes, Caroline Sarah; Weber, Daniela; Wagenpfeil, Stefan; Stuetz, Wolfgang; Moreno-Villanueva, María; Dollé, Martijn E. T.; Jansen, Eugène; Gonos, Efstathios S.; Bernhardt, Jürgen; Grubeck-Loebenstein, Beatrix; Fiegl, Simone; Sikora, Ewa; et al.
Abstract: Self-rated health (SRH) is associated with higher risk of death. Since low plasma levels of fat-soluble vitamins are related to mortality, we aimed to assess whether plasma concentrations of vitamins A, D and E were associated with SRH in the MARK-AGE study. We included 3158 participants (52 % female) aged between 35 and 75 years. Cross-sectional data were collected via questionnaires. An enzyme immunoassay quantified 25-hydroxyvitamin D and HPLC determined α -tocopherol and retinol plasma concentrations. The median 25-hydroxyvitamin D and retinol concentrations differed significantly ( P < 0·001) between SRH categories and were lower in the combined fair/poor category v . the excellent, very good and good categories (25-hydroxvitamin D: 40·8 v. 51·9, 49·3, 46·7 nmol/l, respectively; retinol: 1·67 v. 1·75, 1·74, 1·70 µmol/l, respectively). Both vitamin D and retinol status were independently associated with fair/poor SRH in multiple regression analyses: adjusted OR (95 % CI) for the vitamin D insufficiency, deficiency and severe deficiency categories were 1·33 (1·06–1·68), 1·50 (1·17–1·93) and 1·83 (1·34–2·50), respectively; P = 0·015, P = 0·001 and P < 0·001, and for the second/third/fourth retinol quartiles: 1·44 (1·18–1·75), 1·57 (1·28–1·93) and 1·49 (1·20–1·84); all P < 0·001. No significant associations were reported for α -tocopherol quartiles. Lower vitamin A and D status emerged as independent markers for fair/poor SRH. Further insights into the long-term implications of these modifiable nutrients on health status are warranted.